Effect of frozen storage and hydrocolloids on structural and rheological properties of frozen roti dough supplemented with rice bran - MUADIAD,Khanittha (2022)
Abstract This study investigated the effect of addition of hydrocolloids (hydroxypropyl methylcellulose: HPMC, and xanthan) and frozen storage on the structure and rheological properties of frozen roti dough supplemented with rice bran. The roti dough was frozen by air blast freezing and stored at -18 °C for 84 days. Changes in the protein structure of the frozen roti dough with HPMC produced greater changes in the gluten network and random coil conformations than that of the xanthan supplemented dough during frozen storage. The resistance to extension and the elastic modulus of the frozen roti dough with HPMC tended to decrease while the extensibility slightly increased with a longer frozen storage time. However, these parameters did not change in the frozen roti dough with xanthan. The freezable water in the frozen roti dough with HPMC and xanthan significantly increased (p < 0.05) with increasing frozen storage time from 0 to 84 days.